PENGARUH KARAKTER EKSEKUTIF DAN FINANCIAL DISTRESS TERHADAP TAX AVOIDANCE - Windi Oktavia; Mohamad Safii (LPPM Universitas Bina Bangsa, 2023)
This study aims to determine the effect of Executive Character and Financial Distress on Tax Avoidance in Food and Beverage sub-manufacturing companies listed on the IDX for the 2017-2020 period. This study uses the population in this study using the purpose sampling method. The number of companies studied in this study were 13 sample companies with each observation period of 5 years, so that 65 samples of data were obtained. Sources of data used in this study is secondary data. Data analysis was carried out using Eviews 9. The results of the research simultaneously that Executive Character and Financial Distress had an effect on Tax Avoidance. Partially, the Executive Character has an effect on Tax Avoidance, Financial Distress has an effect on Tax Avoidance